Effect of 5-hydroxytryptamine on protein synthesis in gastrointestinal and other tissues and on serum gastrin concentrations in rats. - Nandi Majumdar, A. P. (Nature Publishing Group, 1979)
1 The effect of 5-hydroxytryptamine (5-HT) on protein synthesis in the gastrointestinal tissues as well as in the liver, heart and brain was studied by measuring [3H]-leucine incorporation into total tissue protein in vivo in rats. 2 A single injection of 5-HT (10 mg/kg) produced a marked inhibition (45 to 65%) in protein synthesis in the stomach (oxyntic gland area), intestine (jejunum + ileum), colon and brain, but not in the liver and heart. 3 Dose- and time-dependent studies of 5-HT-induced changes in protein synthesis in the stomach of fed rats revealed that the maximal inhibition of about 65% occurred 1 h after a dose of 12.5 mg/kg. 4 Animals deprived of food for 24 h differed from their fed counterparts only in the degree of responsiveness, in that a greater inhibition (75%) of [3H]-leucine incorporation into total protein of the stomach was observed 30 min after 5-HT injection. 5 Pretreatment of animals with methysergide (0.25 mg/kg) essentially abolished the 5-HT-mediated inhibition of protein synthesis in the stomach. 6 Serum gastrin concentration in fasted animals remained slightly elevated during the initial period of 5-HT treatment (up to 1 h). 7 The results demonstrate that in certain tissues, 5-HT markedly inhibits protein synthesis. The inhibition in protein synthesis in the gastrointestinal tract cannot be attributed to changes in the concentration of gastrin.